Profit Efficiency of Smallholder Soybean Farmers in Tolon District of Northern Region of Ghana (Ghana Journal of Science, Technology and Development, 2021)
The study aimed to estimate the profit efficiency of soybean producers in the Tolon District of Northern Region of Ghana and identify the sources of inefficiency and production constraints. Data for the study was obtained from 200 smallholder soybean farmers selected using simple random sampling and a structured questionnaire. A translog stochastic profit frontier model was employed to assess profit efficiency and the sources of inefficiency whiles Kendall’s coefficient of concordance was used to rank the production constraints. The results revealed an average profit efficiency of 0.70, indicating a loss of 30% of the potential attainable profit to inefficiency. On the sources of inefficiency, the findings revealed that the combined application of chemical fertilizer and rhizobium inoculant decreased profit inefficiency, whereas application of only chemical fertilizer or rhizobium inoculant increased profit inefficiency. Profit inefficiency also decreased with access to extension, farmer group membership and years of farming experience. Farmers ranked financial constraints, high cost of tractor services and low yields as their most important production constraints. The study recommends that farmers must join groups to enhance their efficiency while extension services must be made accessible to more farmers. Farmers also need training on the recommended application rates of chemical fertilizer and rhizobium inoculants to maximize profit.Keywords: profit efficiency, stochastic frontier analysis, soybean, Ghana